Connexin30.2: In Vitro Interaction with Connexin36 in HeLa Cells and Expression in AII Amacrine Cells and Intrinsically Photosensitive Ganglion Cells in the Mouse Retina - Meyer, Arndt; Tetenborg, Stephan; Greb, Helena; Segelken, Jasmin; Dorgau, Birthe; Weiler, Reto; Hormuzdi, Sheriar G.; Janssen-Bienhold, Ulrike; Dedek, Karin (Frontiers in Molecular Neuroscience, 2016)
Electrical coupling via gap junctions is an abundant phenomenon in the mammalian retina and occurs in all major cell types. Gap junction channels are assembled from different connexin subunits, and the connexin composition of the channel confers specific properties to the electrical synapse. In the mouse retina, gap junctions were demonstrated between intrinsically photosensitive ganglion cells and displaced amacrine cells but the underlying connexin remained undetermined. In the primary rod pathway, gap junctions play a crucial role, coupling AII amacrine cells among each other and to ON cone bipolar cells. Although it has long been known that connexin36 and connexin45 are necessary for the proper functioning of this most sensitive rod pathway, differences between homocellular AII/AII gap junctions and AII/ON bipolar cell gap junctions suggested the presence of an additional connexin in AII amacrine cells. Here, we used a connexin30.2-lacZ mouse line to study the expression of connexin30.2 in the retina. We show that connexin30.2 is expressed in intrinsically photosensitive ganglion cells and AII amacrine cells. Moreover, we tested whether connexin30.2 and connexin36 – both expressed in AII amacrine cells – are able to interact with each other and are deposited in the same gap junctional plaques. Using newly generated anti-connexin30.2 antibodies, we show in HeLa cells that both connexins are indeed able to interact and may form heteromeric channels: both connexins were co-immunoprecipitated from transiently transfected HeLa cells and connexin30.2 gap junction plaques became significantly larger when co-expressed with connexin36. These data suggest that connexin36 is able to form heteromeric gap junctions with another connexin. We hypothesize that co-expression of connexin30.2 and connexin36 may endow AII amacrine cells with the means to differentially regulate its electrical coupling to different synaptic partners.